Recipient outcomes in total laparoscopic live donor nephrectomy with multiple renal vessels - Fitzpatrick, John (Urol Ann, 2020)
INTRODUCTION: In kidney transplantation, total laparoscopic live donor nephrectomy (TLLDN) in the presence of multiple renal arteries (MRA) is technically challenging and has traditionally been associated with higher complication rates. We report our experience of using MRA grafts procured by TLLDN. MATERIALS AND METHODS: Patients undergoing TLLDN at our center (2004–2014) was identified from a prospectively maintained database and divided into single renal arteries (SRA) or MRA groups. Recipient perioperative parameters, postoperative complications, and long-term graft survival were analyzed. RESULTS: Of 465 patients, 106 had MRA and 359 had an SRA. There were six vascular complications in the SRA group and two in the MRA group (1.7% vs. 1.8%). There were eight ureteric complications requiring intervention in the SRA group compared to three in the MRA group (4% vs. 3%; P = 0.45). Acute rejection was observed in 12% of the SRA group compared to 9% in the MRA group (P = 0.23). One-, 5- and 10-year graft survivals were 98.2%, 91.3%, and 89.8% in the MRA group versus 98.0%, 90.4%, and 77.5% in the SRA group (log-rank P = 0.13). CONCLUSION: The use of MRA grafts procured by TLLDN has comparable complication rates to SRA grafts and should not preclude selection for renal transplantation.